Comparative Evaluation on Combustion and Emission Characteristics of a Diesel Engine Fueled with Crude Palm Oil Blends - Jun Cong Ge; Sam Ki Yoon; Jun Hee Song (Applied Sciences, 2021)
Vegetable oil as an alternative fuel for diesel engine has attracted much attention all over the world, and it is also expected to achieve the goal of global carbon neutrality in the future. Although the product after transesterification, biodiesel, can greatly reduce the viscosity compared with vegetable oil, the high production cost is one of the reasons for restricting its extensive development. In addition, based on the current research on biodiesel in diesel engines, it has been almost thoroughly investigated. Therefore, in this study, crude palm oil (CPO) was directly used as an alternative fuel to be blended with commercial diesel. The combustion, engine performance and emissions were investigated on a 4-cylinder, turbocharged, common rail direct injection (CRDI) diesel engine fueled with different diesel-CPO blends according to various engine loads. The results show that adding CPO to diesel reduces the maximum in-cylinder pressure and maximum heat release rate to 30 Nm and 60 Nm. The most noteworthy finding is that the blend fuels reduce the emissions of hydrocarbons (HC), nitrogen oxides (NOx) and smoke, simultaneously. On the whole, diesel fuel blended with 30% CPO by volume is the best mixing ratio based on engine performance and emission characteristics.